Characteristics and dynamics of PTSD in the participants of the Ukrainian anti-terrorist operation - Pustovoyt, Mykhaylo (Psychosomatic Medicine and General Practice, 2018)
The following paper underlines the specific characteristics and the course of Post-traumatic stress disorder (PTSD) in Ukrainian warriors of ATO. It is based on interviews recorded with 163 combatants using the methods of clinical psychology and psychodynamic methods. All the records of the interviews were reflected upon in supervision groups. The data obtained support the hypothesis that the cultural and historical heritage of the people of Ukraine has a determinative pathoplastic effect on the experience of war trauma. The analysis of this data leads to the conclusion about the need to create a favorable system of rehabilitation for veterans that would allow working more successfully with the war trauma.